Methodological procedure based on quantitizing/liquefying: a case study to assess work climate in an emergency department - Chacón-Moscoso, Salvador; Anguera, M. Teresa; Sanduvete-Chaves, Susana; Lozano-Lozano, José A. (Frontiers in Psychology, 2023)
Introduction: In the assessment of health organizations, results-based indicators are mainly used, with no consideration of internal work dynamics. This type of assessment forfeits much of the rich, useful information needed to make decisions on improving the organization. In order to address this, a rigorous procedure based on mixed methods is laid out here on gathering, analyzing, and interpreting data associated with the implementation process. Methods: A 55-year-old doctor was randomly selected at random from among the staff who volunteered to be interviewed at the emergency department at a public hospital located in southern Spain for an interview. Qualitative data obtained from the in-depth interview (indirect observation) were progressively systematized (liquefied and quantized) based on a theoretical framework until a code matrix was obtained, without losing or distorting any information. Afterwards, data quality was controlled using Cohen's kappa (κ) coefficient. A quantitative polar coordinate analysis was then carried out using the free software HOISAN (v. 1.6.3.3) to obtain robust results, vectorizing the relationships between codes and specifying whenever such relationships were statistically significant (and if they resulted in behavior activation or inhibition). Finally, a supplementary quantitative and qualitative assessment was carried out. Results and discussion: The proposed method was applied to the needs assessment of teams in order to evaluate that work climate in the hospital's emergency department Health Services of a hospital.Data quality control yielded an adequate result (κ = 0.82). Significant activation and inhibition of behaviors occurred, both prospectively and retrospectively. For instance, We seek to understand the needs of our clients and We readily adapt to new circumstances showed a significant activation (vector length = 3.43, p < .01) both prospectively (Zsum = 0.48) and retrospectively (Zsum = 3.4). An adequate method to obtain detailed information about group dynamics in a work environment is presented, based on an in-depth interview. Practical applications for implementations to improve the functioning of organizations are presented.